Pengaruh Gross Domestic Product Korea Selatan, Nilai Tukar, dan Kebijakan Dumping terhadap Ekspor Pulp Negara Indonesia Ke Korea Selatan Tahun 2004-2023 - Anggreini, Yola Febi; Widayatsari, Any; Darmayuda, Darmayuda (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
This study aims to examine whether there is an effect of Gross Domestic Product (GDP), exchange rates, and dumping policies on Indonesian pulp exports to South Korea from 2004 to 2023. The data used in this study is secondary time series data. The method used in this study is quantitative analysis, namely multiple linear regression analysis, statistical testing including the F test, t test, and R square, as well as classical assumption testing, namely normality, heteroscedasticity, multicollinearity, and autocorrelation with the help of the Eviews 12 program. The average value of pulp exports to South Korea was USD 170.05 million. The results of this study indicate that GDP has a negative effect on pulp exports to South Korea. The exchange rate has no effect on pulp exports to South Korea. When a dumping policy is in place, it affects pulp exports to South Korea, but after the dumping policy is no longer in effect, it has no effect on Indonesian pulp exports to South Korea.